ESG disclosure and portfolio performance - Ramón Bermejo Climent; Isabel Figuerola-Ferretti Garrigues; Ioannis Paraskevopoulos; Alvaro Santos (Risks, 2021)
This paper illustrates the impact of Environmental Social and Governance (ESG) disclosure on European corporate equity performance. In this study, we use an extensive data set of European ESG ratings provided by Bloomberg to demonstrate that ESG disclosure is associated with improved return growth, with the Governance pillar exhibiting the strongest effect on corporate performance. The impact of ESG disclosure on volatility is changing over time, suggesting that the existence of opaque ratings limits the transmission of information disclosure into corporate performance.
Keywords: 330; ESG investing; excess returns; governance; sustainability; volatility